Effect of nitrogen scheduling on nitrogen uptake pattern and seed protein yield, oil yield and oil quality of canola oilseed rape (Brassica napus) sown on different dates: EFFECT OF NITROGEN ON NITROGEN UPTAKE PATTERN OF CANOLA SOWN ON DIFFERENT DATES - LOVELEEN KAUR; VIRENDER SARDANA; GURPREET KAUR (Journal of Oilseeds Research, 2020)
A field experiment was conducted at the Punjab Agricultural University Ludhiana during rabi 2016-17 to study the effect of nitrogen (N) application dose and time on N uptake pattern, protein and oil yield and oil quality of canola oilseed rape (Brassica napus) under different sowing dates. The treatments comprised three sowing dates (15 October, 30 October and 15 November) in the main plots and seven combinations of dose (100 and 125 kg/ha) and time of application of N (two or three splits) in sub plots. Loamy sand soil of experimental field was low in organic carbon and available N in the upper 15 cm soil profile. The test variety GSC 7 was sown at spacing of 45 cm x 10-12 cm. Delay in sowing significantly reduced the N content and uptake by canola oilseed rape at all growth stages in different plant parts as well as in seed and stover at maturity except N content in stem at 80 DAS. The highest oil yield (941 kg/ha) obtained with 125 kg/ha of N applied as 50 kg at sowing + 50 kg at initiation of stem elongation + 25 kg at initiation of flowering was at par with application of 125 and 100 kg/ha of N in two equal splits at sowing and initiation ofstemelongation. The highest protein yield (738 kg/ha) obtained with 125 kg/ha of N applied in three splits (50 + 50 + 25) was significantly higher than all other treatments. The highest oil yield produced by 15 October sown crop with application of 125 kg/ha of N in three splits (1056 kg/ha) was 7.3% and 40.4%% higher than application of 100 kg/ha of N in two equal splits and 6.7% and 35.9% higher than 125 kg/ha of N in three splits in 30 October and 15 November sown crop, respectively. Fatty acid composition of oil was not influenced by sowing dates and N scheduling.